2018
DOI: 10.1016/j.jpeds.2017.09.047
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carina Position Antenatally and Postnatally in Infants with Congenital Diaphragmatic Hernia

Abstract: Cephalad displacement of the carina in infants with CDH may predispose them to right main-stem intubation and subsequent development of pneumothorax. We speculate that modifying the ETT insertion depth to 5.5 cm + weight in newborns born at term may prevent pneumothoraces and improve outcomes for infants with CDH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Poor prognostic indicators in infants with CDH include cardiac or chromosomal abnormalities, hepatic herniation, lung area/head circumference ratio (LHR) < 25%, percent predicted lung volume (PPLV) < 15%, total lung volume < 20 mL, LV hypoplasia, and right-sided CDH. Infants with a low PPLV had significantly higher rates of extracorporeal membrane oxygenation (ECMO) use [7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Poor prognostic indicators in infants with CDH include cardiac or chromosomal abnormalities, hepatic herniation, lung area/head circumference ratio (LHR) < 25%, percent predicted lung volume (PPLV) < 15%, total lung volume < 20 mL, LV hypoplasia, and right-sided CDH. Infants with a low PPLV had significantly higher rates of extracorporeal membrane oxygenation (ECMO) use [7][8].…”
Section: Discussionmentioning
confidence: 99%
“…described a cephalad displacement of the carina both pre-and postnatally. 30 They found that more severe CDH indices were predictors of a shorter distance from the thoracic inlet to the carina. While they proposed using a shallower ETT depth during initial stabilization, 30 this study suggests a deeper depth than current estimates even in our more severe cases.…”
Section: Manuscriptmentioning
confidence: 97%